Accessing molecular structure and dynamics of photoelectrochemical systems with nonlinear optical spectroscopy - Farah, Yusef Rodney, author; Krummel, Amber T., advisor; Szamel, Grzegorz, committee member; Barisas, B. George, committee member; Bartels, Randy, committee member (Colorado State University. Libraries, 2022)
Photoelectrochemical cells (PEC) are a class of solar energy device that have a variety of applications and can be used to directly generate electricity or convert the sun's energy in the form of chemical bonds through photosynthetic processes. The first PEC dates to Becquerel's discovery of the photovoltaic effect in 1839; and, after nearly 200 years of its first creation, the PEC is constantly evolving with the discovery of new fabrication techniques and materials. Sunlight harvesting materials are used in PECs to capture the sun's radiation and drive electron transfer and photocatalytic reactions. Understanding the photophysical properties of the materials used within PEC chemical systems informs on the development of high-performance, low-cost, and sustainable solar energy devices needed to address current global climate challenges and meet societal energy demands. Chemical systems in PEC architectures are nontrivial and often rely on several components working harmoniously in tandem with one another to stimulate photovoltaic or photocatalytic processes. Dye-sensitized solar cells (DSSCs) are a type of photovoltaic PEC that use molecular chromophores to absorb light, transfer electrons to a semiconductor, and accept electrons from an electrolyte. Local environmental structure of the chromophore can either promote or hinder these electron transfer events within a device. To this end, investigating the molecular structure of the chromophore, including the parameters that influence the structure, is necessary for fabricating DSSCs with optimal efficiency. The work presented in this dissertation utilizes the nonlinear optical spectroscopic technique of heterodyne-detected vibrational sum frequency generation (HD-VSFG) to investigate the interfacial structure of N3-dye, a popular chromophore used within DSSC devices. It is discovered that the interfacial structure of N3 is influenced by the substrate, pH conditions upon deposition to the substrate, and by the presence of an electrolyte. Additionally, the work presented herein investigates exciton dynamics of monolayer MoS2 photoanodes within an operational PEC. Monolayer transition metal dichalcogenides (TMDs), such MoS2, are two-dimensional semiconducting materials with fascinating photophysical properties. Only recently have monolayer TMDs been investigated for their integration within optoelectronic devices, such as PECs. By utilizing ultrafast transient absorption (TA) spectroscopy, unique exciton properties of the MoS2 photoanode are identified within operational conditions. Photocurrent generation via ultrafast hot carrier extraction is discovered, challenging the preconceived notions of the Shockley-Queisser limit; further, we explore the dynamic control of the exciton energy by tuning an external voltage bias to the PEC. PEC chemical environments are ubiquitous and the photophysical properties are dependent on many underlying parameters. Set forth in this dissertation is the foundation for applying the nonlinear optical techniques of HD-VSFG and TA across a variety of chemical systems pertaining to PECs and assessing data within an established theoretical framework to elucidate molecular structure and dynamics.